Facilitators and Barriers to Sustainable Employment After Spinal Cord Injury or Acquired Brain Injury: The Person's Perspective - Karcz, Katarzyna; Schiffmann, Barbara; Schwegler, Urban; Staubli, Stefan; Finger, Monika E. (Frontiers in Rehabilitation Sciences, 2022)
Background Sustaining employment after initial return to work represents a major challenge for people with a disability. While individuals with spinal cord injury (SCI) and acquired brain injury (ABI) make a prime example for this challenge, their view on factors supporting and hindering sustainable employment have rarely been investigated in depth so far. Purpose To examine facilitators and barriers to sustainable employment, as perceived by persons with SCI or ABI. Methods Fourteen focus groups and four individual interviews were conducted and thematically analyzed. Results Perceived facilitators and barriers to sustainable employment reflected the three biopsychosocial areas of personal, impairment-related and environmental factors. For both condition groups, key facilitators included environmental factors (i.e., aspects of the work organization, the workplace, supportive private and work environment) and personal factors (i.e., the ability to self-advocate, to communicate and to learn how to live with one's own disability). Major barriers comprised injury-related impairments, including decreased mobility and pain for people with SCI and fatigue and limited cognitive resources for persons with ABI, as well as environmental factors related to insurance procedures and the social security system for both conditions. Conclusions The biopsychosocial factors identified in our study as well as their interplay should receive particular attention to optimally support sustainable employment in vocational integration and work retention practice. Interventions should particularly focus on the empowerment of those affected as well as on the creation of supportive work environments that match their abilities and needs.